Inovasi Cheesecake Menggunakan Bahan Kacang Buncis sebagai Pengganti Terigu - Yuliantoro, Nonot (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
Making cheesecake using string bean is one of the latest innovations in making cheese cake that has never been seen before. Cheesecake generally use flour, this study aims at how string bean can be used as an ingredient of chiffon cheesecake by drying and processing into vegetable flour. This research was conducted to find out whether vegetable flour can affect the texture, taste, aroma and color of cheesecake. The purpose of string bean as a substitute for wheat flour is for consumption for the general public, especially for those who cannot consume gluten and make an alternative for people who do not like vegetables. In this study, we have conducted several vegetable group studies ranging from vegetable, leaf, stem, flower and fruit groups. Then found the right vegetable group to be made as a component of cheesecake, namely fruit vegetables. In addition, modifications are also made to the recipe, especially on the amount of vegetable flour. Excessive amounts will greatly affect the taste, texture, and aroma of the cheesecake. This study uses the homemade method. Homemade, which is meant by itself, is the making of using equipment that is few and can be made by anyone with the right technique.